2012
DOI: 10.3389/fneur.2012.00047
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Asymmetry in Insomnia Sufferers

Abstract: Cerebral asymmetry is used to describe the differences in electroencephalographic activity between regions of the brain. The objective of this study was to document frontal, central, and parietal asymmetry in psychophysiological (Psy-I) and paradoxical (Para-I) insomnia sufferers as well as good sleeper (GS) controls, and to compare their patterns of asymmetry to others already found in anxiety and depression. Additionally, asymmetry variations between nights were assessed. Participants were 17 Psy-I, 14 Para-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 66 publications
2
30
0
1
Order By: Relevance
“…Although, by far, there is no clear evidence about asymmetric effects of insomnia on the brain, previous studies have also reported lateralized patterns of brain structural alterations in PI [ 67 69 ]. It is plausible that the asymmetric structural changes may be related to the abnormal functional asymmetries in patients with PI during night or sleep [ 70 , 71 ]. In addition, we also noted that only the SCNs of the primary auditory and olfactory regions showed statistically significant alterations in patients with PI (survived in the multiple comparison correction), but the SCNs of the primary visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Although, by far, there is no clear evidence about asymmetric effects of insomnia on the brain, previous studies have also reported lateralized patterns of brain structural alterations in PI [ 67 69 ]. It is plausible that the asymmetric structural changes may be related to the abnormal functional asymmetries in patients with PI during night or sleep [ 70 , 71 ]. In addition, we also noted that only the SCNs of the primary auditory and olfactory regions showed statistically significant alterations in patients with PI (survived in the multiple comparison correction), but the SCNs of the primary visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Frontal EEG asymmetry has been described as a marker for affective style, with left and right frontal cortex associated with approach and withdrawal tendencies, respectively (Davidson et al 1990). Other reports have associated hemispheric oscillatory asymmetry with posttraumatic stress disorder (Rabe et al 2006;Engdahl et al 2010), insomnia (St-Jean et al, 2012), attention-deficit disorder (Hale et al 2010), autism (Stroganova et al 2007;Lazarev et al 2010), dyslexia (Spironelli et al 2008), and schizophrenia (Swanson et al 2010). Whether there could be a physiologic disturbance common to these asymmetries has not been much considered, but the hemispheric lateralization of management of the autonomic nervous system functioning (Yoon et al 1997;Avnon et al 2004;Craig 2005)sympathetic and parasympathetic divisions by the right and left hemispheres, respectivelyseems to raise the possibility that hemispheric oscillatory asymmetry may be an indicator of dysregulation of autonomic nervous system functioning.…”
Section: Disturbances Of Neural Oscillationmentioning
confidence: 99%
“…; Engdahl et al. ), insomnia (St‐Jean et al., ), attention‐deficit disorder (Hale et al. ), autism (Stroganova et al.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps, finer REM sleep microstructure variables such as the density of the activities in the different frequency bands measured using PSA might be a better reflection of this heightened arousal in insomnia. Limited literature exists on this subject, but so far, results obtained using PSA tend to show significant differences between PSY-I, PARA-I and GS in the density of each frequency bands during REM sleep (Freedman, 1986;Krystal et al, 2002;Merica et al, 1998;Perlis et al, 2001;St-Jean et al, 2012. Therefore, it seems that this finer aspect of REM sleep microstructure is somehow related to the hyperarousal typically suggested in INS.…”
Section: Psy-imentioning
confidence: 83%